Investigation of atomic layer deposited thin film for protection of BiVO4 photo-anodes in photoelectric cells - Kumaresan, Heeran (2018)
The ongoing demand for clean energy means we have to find ways to produce this energy and photo-electrical chemical cells (PEC) is an attractive method to produce hydrogen fuel from solar energy. BiVO4 is a suitable material used for the photo-anode in the PEC method due to its good band gap and charge transport properties. However, photo-corrosion is a big problem and this degradation problem reduces the stability of the photo-anode which subsequently reduces the performance capability and efficiency of the hydrogen fuel production. To combat this photo-corrosion problem, a protective layer over the photo-anode is needed and this layer should have sufficient charge transport properties to allow the diffusion of electrons and holes besides being transparent to light. Hence, we chose to evaluate TiO2 deposited by atomic layer deposition as a protective layer for Mo-BiVO4 photo-anode whose performance was evaluated in a PEC setup in the laboratory. Firstly, after comparing the data obtained from linear sweep voltammetry method, the photocurrent density increases with increasing applied voltage after illumination. However, for a sample coated with TiO2, the amount of photocurrent generated is slightly lower compared to a sample that is not coated with TiO2 at a particular voltage. This was due to extra energy having to penetrate the layer of TiO2 which would result in lesser number of electrons and holes generated for transport. Next, we used a chronoamperometry scan to determine the stability of the photo-anode. We analysed both the TiO2 coated sample and non-TiO2 coated sample and found that there was no depreciation in photocurrent density with respect to time for the coated sample. However, the photocurrent density depreciated significantly with time for the non-coated sample, concluding that TiO2 is indeed an effective protective layer for photo-corrosion. Understanding the protective mechanism of TiO2 and evaluating the data obtained is important to determine the suitability of TiO2 for this application.